HUBUNGAN LAMA PENGGUNAAN SMARTPHONE DENGAN TINGKAT PRESTASI BELAJAR PADA SISWA KELAS III SAMPAI V DI SDN 03 BINUANG KAMPUNG DALAM PAUH, KOTA PADANG - Rahmad Saputra; Nurhaida; Sari, Yunita Purnama (BPPM Politeknik 'Aisyiyah Sumatera Barat, 2024)
Nowadays smartphones have become a fast and efficient information search tool, in addition to increasing knowledge and as a medium of entertainment and expanding social networks. However, among school students’ smartphones have many disadvantages, especially on the learning outcomes of students. Research conducted at SD N 03 Binuang Kampung Dalam found 7 students (25.92%) who used smartphones for more than 2 hours and had a low level of achievement. This study aims to determine the relationship between the length of smartphone use and the level of student achievement. This type of research is an analytic method with a cross-sectional approach. The study population was all students in grades 3, 4, and 5. Sampling using total sampling which amounted to 84 students. research was conducted by distributing questionnaires and observation sheets. Data analysis used was univariate and bivariate analysis. The results showed that most of the students at SD N 03 Binuang Kampung Dalam long use of smartphones as many as 53 respondents (63.1%). Statistical tests concluded that there was a significant relationship (p=0.000) between the length of smartphone use and the level of learning achievement in students. It is expected that schools and parents can control the length of time playing smartphones in children in order to minimize the negative impact of smartphones so as not to affect the level of learning achievement at school.